2020
DOI: 10.1371/journal.pone.0234186
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of topical bevacizumab 0.05% eye drops in dry eye disease: A double-masked, randomized trial

Abstract: The objective of this double-masked, placebo-controlled, randomized trial was to assess the efficacy and safety of bevacizumab 0.05% eye drops in dry eye patients. This study included Dry Eye Workshop Study (DEWS) Grade 3-4 dry eye participants (n = 31) whose tear break-up time (TBUT) was �5 seconds(s). Participants were randomized to undergo treatment with either bevacizumab 0.05% eye drops (n = 19) or placebo (n = 12). The primary outcome was TBUT, and the proportion of responders (increase of �3s in TBUT at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(41 reference statements)
0
7
0
1
Order By: Relevance
“…Finally, 56 articles were included in the meta-analysis. As a placebo, the studies included in this meta-analysis used saline [ 30 , 33 , 34 , 37 , 45 , 47 , 48 , 53 , 57 , 71 , 72 , 74 , 77 ] or balanced salt solution [ 35 ], vehicle drops [ 29 , 43 , 50 , 52 , 56 , 61 , 66 68 , 80 ], artificial tears [ 81 ], sham pulsed light treatment [ 55 , 78 ], sham acupuncture [ 92 ], an ophthalmic solution containing base only [ 36 ], oral vitamin E [ 39 ], olive oil [ 7 , 42 , 44 , 51 , 70 , 75 , 83 ], sunflower oil [ 59 , 85 ], safflower oil [ 84 ], wheat germ oil [ 65 ], corn oil [ 54 ], palm and coconut oil [ 62 , 63 ], medium-chain fatty acids [ 60 ], or tablets without the active ingredient with the same appearance as the active treatment [ 40 , 46 , 49 , 58 , 69 , 79 ], placebo beverage with a similar texture, flavour, and taste as the active agent [ 31 ],1000 IU of vitamin A in a study using 100,000 IU of vitamin A as active treatment [ 76 ], or the placebo was not exactly specified [ 9 , 41 , 73 , 82 ]. Therefore, the choice of placebo was heterogenous.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 56 articles were included in the meta-analysis. As a placebo, the studies included in this meta-analysis used saline [ 30 , 33 , 34 , 37 , 45 , 47 , 48 , 53 , 57 , 71 , 72 , 74 , 77 ] or balanced salt solution [ 35 ], vehicle drops [ 29 , 43 , 50 , 52 , 56 , 61 , 66 68 , 80 ], artificial tears [ 81 ], sham pulsed light treatment [ 55 , 78 ], sham acupuncture [ 92 ], an ophthalmic solution containing base only [ 36 ], oral vitamin E [ 39 ], olive oil [ 7 , 42 , 44 , 51 , 70 , 75 , 83 ], sunflower oil [ 59 , 85 ], safflower oil [ 84 ], wheat germ oil [ 65 ], corn oil [ 54 ], palm and coconut oil [ 62 , 63 ], medium-chain fatty acids [ 60 ], or tablets without the active ingredient with the same appearance as the active treatment [ 40 , 46 , 49 , 58 , 69 , 79 ], placebo beverage with a similar texture, flavour, and taste as the active agent [ 31 ],1000 IU of vitamin A in a study using 100,000 IU of vitamin A as active treatment [ 76 ], or the placebo was not exactly specified [ 9 , 41 , 73 , 82 ]. Therefore, the choice of placebo was heterogenous.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 56 articles were included in the meta-analysis. As a placebo, the studies included in this meta-analysis used saline [30,33,34,37,45,47,48,53,57,71,72,74,77] or balanced salt solution [35], vehicle drops [29,43,50,52,56,61,[66][67][68]80], artificial tears [81], sham pulsed light treatment [55,78], sham acupuncture [92], an ophthalmic solution containing base only [36], oral vitamin E [39], olive oil [7,42,44,51,70,75,83], sunflower oil [59,85], safflower oil [84], wheat germ oil [65], corn oil [54], palm and coconut oil [62,63], medium-chain fatty acids [60], or tablets without the active ingredient with the same appearance as the active treatment [40,…”
Section: Study Selectionmentioning
confidence: 99%
“…Despite evidence that high concentrations of bevacizumab (∼5.00 mg/mL) may be toxic to the corneal epithelium, very low concentrations of topical bevacizumab are being explored as an effective modality against OSD. In a recent randomized, controlled clinical trial, Kasetsuwan et al 10 assessed the safety and efficacy of bevacizumab 0.05% (0.5 mg/mL) eye drops as a novel treatment for dry eye disease (DED) in 31 participants, and they concluded that all participants had improvement in tear break-up time, an important diagnostic sign in DED, over the 12-week follow-up period with no adverse events. Thus, this may be considered as an alternative treatment for DED to decrease inflammation as opposed to the use of steroids and cyclosporin-A, which can have adverse events, such as elevated intraocular pressure, cataract, and burning or stinging symptoms.…”
Section: Of Vitreous)mentioning
confidence: 99%
“…Двойное слепое, плацебо-контролируемое рандомизированное исследование эффективности бевацизумаба 0,05 % в виде глазных капель для лечения БСГ III-IV cтепени (время разрыва слезной пленки менее 5 с) показало, что на фоне инстилляций бевацизумаба чаще увеличивалось время разрыва слезной пленки, более значительно снижался индекс OSDI по сравнению с плацебо. Не было выявлено побочных эффектов применения бевацизумаба 0,05 % в виде глазных капель при лечении БСГ [22].…”
unclassified